The Implementation of Online Learning Methods During the Covid-19 Pandemic in Geography Subjects on the Learning Outcomes of Grade XI MIA 1 Students at SMA Negeri 4 Ambon - Andipranata, Wisnu; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
The purpose of this research is to examine the implementation of online learning methods during the COVID-19 pandemic on the learning outcomes of Grade XI MIA 1 students at SMA Negeri 4 Ambon. The results of this study are expected to provide benefits for students, teachers, schools, and study programs. This research employs a qualitative method with a descriptive approach. The research location is SMA Negeri 4 Ambon, situated on Jalan Wolter Monginsidi Lateri, Baguala District, Ambon City, Maluku Province. The subjects of this study are 36 students from Grade XI MIA 1, with a sample of 11 students and 1 geography teacher. The research variables include online learning and student learning outcomes. The research techniques used are interviews and documentation. The data analysis technique employed is qualitative data analysis, where the data collected is presented and analyzed descriptively qualitatively. The highest score among the 36 students in the knowledge category was 86, while the highest score in the skills category was also 86. The lowest score in the knowledge category was 84, and the lowest score in the skills category was 83. The online learning process carried out includes learning administration, the implementation of learning, assessment of learning outcomes and processes, monitoring of the learning process, and students' learning outcomes or report card grades.